A Case Report and Literature Review of Oligomeganephronia - Wang, Xu-Hao; Pan, Lei; He, Shan; Kong, De-Lei; Wang, Wei (Frontiers in Medicine, 2022)
A 23-year-old woman was admitted to the hospital with proteinuria and mildly elevated creatinine, and a renal biopsy confirmed the diagnosis of oligomeganephronia (OMN). OMN is an extremely rare bilateral renal hypoplastic disease, and its diagnosis mainly relies on the pathological results obtained from renal biopsy. At present, there is no effective treatment for OMN. Here, we report a case with mild renal insufficiency and proteinuria as the main symptom and present a summary of the clinical characteristics of ON along with a review of the literature on OMN.